Serum periostin is associated with prevalent knee osteoarthritis and disease incidence/progression in women: the OFELY study. Issue 10 (October 2015) - Rousseau, J.C.; Sornay-Rendu, E.; Bertholon, C.; Garnero, P.; Chapurlat, R.
Summary: Objective: Our aim was to investigate the relationships between serum periostin (POSTN) and both prevalence and incidence/progression of knee osteoarthritis (OA) in women. Methods: We investigated 594 women (62.7 ± 11.2 yr) from the OFELY cohort. Knee radiographs were scored according to the Kellgren & Lawrence (KL) grading system at baseline and 4 years later. Spine, hip and hand OA were assessed at baseline. Prevalent knee OA was defined by a KL score higher or equal in 2. Progression of KL was defined as an increase of the KL score ≥1 during the 4 years follow-up. Serum POSTN was measured at baseline by ELISA. Results: By non-parametric tests, POSTN was significantly lower in 83 women with a KL score ≥2 at baseline, compared to those with a KL score <2 ( n = 511; 1101 ± 300 vs 1181 ± 294 ng/ml, P = 0.002) after adjustment for age, body mass index (BMI), treatments and diseases, prevalent hand OA and prevalent lumbar spine OA. By logistic regression analyses, the odds-ratio of knee OA incidence/progression was significantly reduced by 21% ( P = 0.043) for each quartile increase in serum POSTN at baseline, after adjustment for age, BMI, prevalent knee OA, prevalent hand OA and prevalent lumbar spine OA. Conclusions: We show for the first time that serum POSTN is associated with prevalence and the risk of development/progression of knee OA in women.